Involute curves of timelike biharmonic reeb curves (LCS) 3-manifolds - Körpinar, Talat; Turhan, Essin; Asil, Vedat (My University, 2012)
In this paper, we study involute timelike biharmonic Reeb curves in (LCS) 3-manifold. We characterize curvatures of timelike biharmonic Reeb curves in (LCS) 3-manifold. We obtain parametric equation involute curves of the timelike biharmonic Reeb curves in (LCS) 3-manifold. © Electronic Journal of Theoretical Physics.
Keywords: (LCS) 3-manifold; Bienergy; Reeb vector field